2011
DOI: 10.3168/jds.2011-4484
|View full text |Cite
|
Sign up to set email alerts
|

Validity of prepartum changes in vaginal and rectal temperature to predict calving in dairy cows

Abstract: The prevalence of dystocia is high in many dairy herds and is associated with stillbirth and negative effects for the cow. An accurate predictor of calving would enable supervision of cows more precisely to a relevant time interval so that obstetrical assistance can be provided in a timely manner. This might help to decrease calf mortality rate. Evidence exists that cows exhibit a decrease in body temperature before the onset of calving. The performance of a decrease in body temperature as a test to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
118
4
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 25 publications
9
118
4
11
Order By: Relevance
“…Recently, several studies measured BT more frequently in the vagina [12,17,18] or the reticulum [19]. Using technologies that allow automatic and frequent recording of BT in dairy cows opens up the opportunity to gain specific information about BT and related management routines under practical on-farm conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies measured BT more frequently in the vagina [12,17,18] or the reticulum [19]. Using technologies that allow automatic and frequent recording of BT in dairy cows opens up the opportunity to gain specific information about BT and related management routines under practical on-farm conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of parturition in cattle has been investigated using real-time ultrasound (Wright et al, 1988), changes in body temperature (Burfeind et al, 2011), blood 17-β-estradiol (Shah et al, 2007) or progesterone profile (Matsas et al, 1992), relaxation of pelvic ligament (Dufty, 1971), electrolyte concentration in mammary secretions (Bleul et al, 2006), intravaginal insert devices that are activated when pushed out of the vagina by the AS (Palombi et al, 2013), and video monitoring of cows before calving (Cangar et al, 2008). The technology to monitor physical cow activity for reproduction (Aungier et al, 2012;Kamphuis et al, 2012;Chebel et al, 2013) or rumination (Reith and Hoy, 2012) as well as health events (e.g., locomotion; Chapinal et al, 2011) are management tools available for dairy herds.…”
mentioning
confidence: 99%
“…Studies using Holstein cattle have shown a good correlation between vaginal and rectal temperatures [24, 25]. While it is difficult to place a short-term internal temperature-measuring device in the rectum, intravaginal placement is relatively easy.…”
Section: Discussionmentioning
confidence: 99%